Penggunaan Media Digital Dalam Pelayanan Bimbingan Dan Konseling Di Masa Pandemi - Latiffatunnisa (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the use of digital media in guidance and counseling (G&C) services during the COVID-19 pandemic, as well as to evaluate the effectiveness, challenges, and benefits experienced by counselors and students. The research employs a mixed methods approach, combining quantitative data from questionnaires and qualitative data from in-depth interviews. The study sample consists of students and counselors from several schools that have implemented remote G&C services during the pandemic. The findings indicate that the majority of both students and counselors felt that remote G&C was effective in providing emotional and psychological support. The main advantages of this service include flexibility in scheduling and greater accessibility from home. However, significant challenges were identified, including limitations in devices, poor internet quality, and difficulties in non-verbal communication, which affect the quality of counseling interactions. Additionally, data privacy issues emerged as a key concern in the implementation of remote G&C services. Despite these challenges, the study suggests that digital media has the potential to remain an integral part of G&C systems in the future, with necessary adjustments and developments in technical and ethical aspects. The research recommends improving technical training for both counselors and students and ensuring robust data privacy protection in remote G&C services.